PAUD Teachers' Capabilities in Utilizing Information and Communication Technology (ICT) in Learning - Ai Nursetiawati; Agustin, Mubiar; Mariyana, Rita (Universitas Pendidikan Ganesha, 2024)
The ability of early childhood education (PAUD) teachers to utilize information and communication technology (ICT) is crucial for maximizing the learning process in today’s digital era. However, there are still obstacles and challenges faced by teachers in effectively integrating ICT into teaching and learning activities. Therefore, this study aims to analyze the level of PAUD teachers’ competence in using ICT and to identify various barriers that hinder its implementation. This research employs a qualitative descriptive approach with research subjects consisting of 6 school principals and 12 PAUD teachers. Data collection techniques included documentation studies in the form of surveys, questionnaires, and interviews. Data analysis used interactive techniques from Miles and Huberman. The results show that all aspects of ICT utilization in early childhood education namely ICT understanding (80.55%), curriculum and assessment (83.33%), pedagogy (77.77%), ICT use (80.55%), organizational and administrative functions (87.03%), and teacher professional development (83.33%) fall into the good category and demonstrate optimal implementation. It can be concluded that PAUD teachers have adequate competence in utilizing information and communication technology to support the learning process. This implies that enhancing PAUD teachers’ ICT skills is essential to support innovative and relevant learning in line with current developments.